State Protection Against Corona Virus Disease 2019 Based On Emergency Constitutional Law - Firman Freaddy Busroh; Fatria Khairo (IHSA Institute, 2022)
The purpose of this study is to find out how the development of Covid-19 in Indonesia impacts people’s lives and how the steps taken by the government to deal with the Covid-19 Pandemic are based on the Study of Emergency Constitutional Law. This research will be carried out using normative legal research methods. The study results found that according to the Indonesian Emergency Constitutional Law, the Indonesian state recognizes emergency conditions with two terms: Dangerous Conditions & Forced Emergencies. Regarding the Covid-19 Pandemic from the perspective of this emergency constitutional law, as well as looking at the policies and legal instruments set by the President, it can be concluded that the President did not categorize Covid-19 in the dangerous category but entered the second terminology, namely Forced Urgency according to the with Article 22 of the 1945 Constitution